Screening of Some Hamamelitannin Derivatives against Staphylococcus Aureus: A Computational Perspective (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Methicillin-resistant Staphylococcus aureus (S. aureus) is a common target for inhibiting the quorum sensing biofilm formation. Hamamelitannin (HAM) has a promising activity to combat these biofilm-associated infections and is used as a quorum sensing inhibitor (QSI). Here, we found different tested derivative compounds for designing S. aureus biofilm inhibitors by functionalization at various positions of HAM. In silico studies were carried out to find better drug candidature. Out of all, 14 derivatives have satisfied higher binding affinity as well as interactions against three different S. aureus target receptors, compared to HAM. DFT, ADME, and toxicity analysis are also performed for these compounds. The stability of the protein-ligand complexes is quantified by 30 ns molecular dynamics simulations. From these various studies, 14 ligands will be considered as potent inhibitors against S. aureus biofilm formation after successfully screening of in vitro and in vivo analysis.